Design of actuator motor acceleration model in dual axis tracker movement for stand-alone PV system - Satria, Habib; Syah, Rahmad B.Y; Silviana, Nukhe Andri; Syafii, Syafii (Institute of Advanced Engineering and Science, 2024)
Stand-alone photovoltaic system or PV is a power generation technology with potential that is environmentally friendly and also one of the solutions for saving high electricity rates today. However, problems that often occur due to weather fluctuations that are always changing, especially North Sumatra, Indonesia result in the conversion produced by solar cells not being optimal. Therefore, it is necessary to do a new model with a dual tracker system and the development of accelerator motor actuators so that the resulting energy conversion is more optimal. The result of optimizing the reliability of the polycrystalline type solar panel which is designed with an additional photovoltaic tracker system to maximize the conversion of solar energy to solar panels is to obtain an output power of 303.72 volts DC and 267.52 volts DC in the position where the tracker is not used. Then the percentage increase in energy reached 29.80%. Dual axis tracker technology is able to maximize energy conversion in improving PV usage performance. The implementation of a stand-alone PV system will be beneficial if the installation is in Indonesian territory, especially in disadvantaged, frontier and outermost areas.